An An Assessment of Employee Engagement: Understanding Organisation with Employees to Increase High Performance - Daryono Daryono (Journal of Business & Management, 2023)
Human resource management (HRM) is a critical component of every firm that focuses on the success of each individual employee. Employee contentment is now regarded to assist employees in performing at a higher level. The new aims of this study is to assess the degree of work engagement and the effect of job insecurity and ethical leadership on work engagement. To quantify work engagement, the aspects of work engagement were measured using a survey approach. Job instability and ethical leadership are also used in this study to investigate how they affect work engagement. This study was carried out through a survey with a data collection instrument in the form of a questionnaire containing a series of structured questions. The questionnaire includes statements that describe the dimensions and variables that were investigated. In this study, the population consists of 225 employees from the Faculty of Economics and Business at Universitas Jenderal Soedirman. The researchers used stratified proportional random sampling. Simple regression analysis and moderated regression analysis were used in this study. The highest level of work engagement found in the opportunity and corporate support dimensions, followed by the job dimension, and the lowest level is found in the organisational dimension.